2019
DOI: 10.1016/j.jcat.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

A site-sensitive quasi-in situ strategy to characterize Mo/HZSM-5 during activation

Abstract: The active sites on the methane dehydroaromatization (MDA) catalyst Mo/HZSM-5 are very hard to characterize, because they are present in various geometries and sizes and only form under reaction conditions with methane at 700 ºC. To address these issues an experimental strategy is presented that enables distinguishing different active sites for MDA present on Mo/HZSM-5 and helps determining the Mo charge, nuclearity and chemical composition. This approach combines a CO pretreatment to separate the active Mo si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 87 publications
4
45
0
Order By: Relevance
“…3,13,[32][33] This transformation marks the 'activation period' of the catalyst as benzene is only produced after Mo (oxy-)carbides are formed (Scheme 1). [34][35] We found that this activation can also be achieved with a pre-treatment under CO atmosphere, which leads to an equivalent active phase of Mo. 36 During this treatment, no carbonaceous deposits are formed as would during activation in CH4.…”
Section: Introductionmentioning
confidence: 88%
“…3,13,[32][33] This transformation marks the 'activation period' of the catalyst as benzene is only produced after Mo (oxy-)carbides are formed (Scheme 1). [34][35] We found that this activation can also be achieved with a pre-treatment under CO atmosphere, which leads to an equivalent active phase of Mo. 36 During this treatment, no carbonaceous deposits are formed as would during activation in CH4.…”
Section: Introductionmentioning
confidence: 88%
“…However, a strong debate (Section S2.1) about the structure of active Mo sites (MoO x C y , Mo x C y etc. ), location (pore surface vs. external surface) and their role in the reaction mechanism is still to be resolved . Besides the ongoing debates regarding the active sites, gaining insight into the initial C−C bond formation mechanism and further oligomerization–cyclization of the intermediates is critical.…”
Section: Introductionmentioning
confidence: 99%
“…Lewis acidity of zeolites has been widely used in heterogeneous acid catalysis. [128][129][130][131] The Lewis acidity originates from substituted Al (III) in the frameworks of zeolites. In the process of zeolite-templated methods, polycyclic aromatic compounds are liable to deposit on the acidic sites, [132] which has positive effect on the formation of nanocarbon structures inside the nanochannels of zeolites.…”
Section: Lewis Aciditymentioning
confidence: 99%